2013
DOI: 10.4028/www.scientific.net/amr.634-638.632
|View full text |Cite
|
Sign up to set email alerts
|

Study on α-Pinene Isomerization over MCM-41 Supported SO<sub>4</sub><sup>2-</sup>⁄TiO<sub>2</sub>

Abstract: Mesoporous MCM-41 molecular sieve was synthesized hydrothermally and selected tetraethoxysilane as silica source. Solid superacid was supported on MCM-41 by dipping and roasting. The samples were characterized by XRD, TEM, and FT-IR. Solid superacid evenly dispersed on MCM-41 with a good pore structure. Their catalytic activities were evaluated in the isomerization of α-pinene. The results show that samples had a good conversion rate and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The prepared SO 4 2À /ZrO 2 -SiO 2 porous spheres exhibited higher catalytic activity than the solid acid catalyst. Dai et al 21 synthesized MCM-41 supported solid superacid catalysts with different loadings. The results showed that SO 4 2À /TiO 2 was uniformly dispersed on the surface of the pore structure of MCM-41.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared SO 4 2À /ZrO 2 -SiO 2 porous spheres exhibited higher catalytic activity than the solid acid catalyst. Dai et al 21 synthesized MCM-41 supported solid superacid catalysts with different loadings. The results showed that SO 4 2À /TiO 2 was uniformly dispersed on the surface of the pore structure of MCM-41.…”
Section: Introductionmentioning
confidence: 99%